Revision of the whitefly genus, Asterochiton Maskell (Hemiptera: Aleyrodidae) from New Zealand, a study of intraspecific variation - Martin, Nicholas A. (Zootaxa, 2020)
All the specimens of Asterochiton species (Hemiptera: Aleyrodidae) on slides in the New Zealand Arthropod Collection, Auckland, were examined. The study reveals that the genus is currently restricted to New Zealand and is redescribed here. Obvious generic characters are the sub-elliptical to sub-circular puparium with distinct invaginations at the thoracic and caudal pores. Seven species are described: Asterochiton asteliae sp. n. from Astelia trinervia (Asteliaceae), and A. arboreae sp. n., A. areolatae sp. n., A. foetidissimae sp. n., A. propinqua sp. n., A. rhamnoidis sp. n., and A. rotundifoliae sp. n. from small-leaved Coprosma spp. (Rubiaceae). There are now 12 named species of Asterochiton, but the Brazilian species, Asterochiton auricolor (Bondar, 1923), does not belong in the genus. Details of minute setae, previously overlooked in described species, are provided. The setae length was found to vary at specific positions. Two species infesting three species of Pittosporum (Pittosporaceae) were observed having long and short setae on the abdomen, sometimes varying within a population from a single tree/host. Asterochiton pittospori Dumbleton is therefore synonymized with A. simplex. Additionally, the location of some setae varied on the subdorsal/submarginal area within a puparium. Chaetotaxy for Asterochiton species is proposed. A key to the puparia of Asterochiton species is provided.